Diseño de tejidos planos con la incorporación de la simbología del pueblo Otavalo - Lema Jimbo, Chaska Pacarina (2023)
The pre-Columbian symbols present in the Andean cultures are a historical legacy that transcends through time and has been valued by locals and strangers due to its cultural value, these graphic symbols are still present in the crafts of each region. This project focuses on the pre-Columbian symbology of the Kichwa Otavalo culture, for which a bibliographic survey was conducted, which was necessary in order to know the historical background of the textile tradition that characterizes this people and the events that influenced over time so that they have lost interest in spreading their culture to the point of adapting cultural aspects of other peoples such as symbology, and sell them as symbols of the Kichwa Otavalo culture. To contribute with a series of designs based on the pre-Columbian symbols of the Kichwa Otavalo culture, applying the basic principles of design and these can be incorporated into the catalog of designs of the company Aly Textiles. Prior to the realization of the design proposals, interviews were conducted with a sample of textile companies dedicated to the production and commercialization of traditional textiles in Otavalo in order to know the interest of the companies in incorporating these new designs to their product catalog as a tool to increase their sales and position themselves in the market.